Kompetensi Profesional dan Sosial Sebagai Prediktor Literasi pada Kinerja Guru Pendidikan Jasmani - Masrun Masrun (Jurnal Patriot, 2021)
This research aimed to analyzed the effect of professional and social competences as a main competency component which give effect toward the physical educators performance. The performance assessment as an urgent mechanism to push desirable behavior of teacher based on Teacher Act. This research using correlational design with associative causal methods for collecting an information from 67 sample, which was an high school physical educator in Padang city West Sumatra. The data collected by questionnaire focus grup discussion. To account the effect of this study, researchers using IBM SPSS software. The result shows there is the differences between male and female teachers on professional and social competences with the physical educators performance. The power of direct effect identified that significantly giving positive f effect toward physical educators performance. For that reason, professional and social competence becoming the main factor in achievement of physical educators teachers.